Roman General’s Attitude against the enemy (200-167 BC): Three Case Studies - José Antonio MARTÍNEZ MORCILLO (Studia Historica: Historia Antigua, 2017)
This paper aims to analyze jointly the campaigns led by three magistrates (l. Emilio Paulo, Q. Fulvius Flaccus and ti. Gracchus) who took part in Hispania as praetores and subsequently developed their consulates in different territories, focusing specifically on the terms imposed on surrendered enemies. the objective is to determine the existence of an evolution of the modus operandi of the imperatores throughout their military career, taking into account the attitude towards the surrendered enemies, and linking this evolution to the general framework of aristocratic rivalry.